HUBUNGAN MOTIVASI PASIEN DENGAN PELAKSANAAN MOBILISASI DINI PASCA SECTIO CAESARIA DI RSIA STELLA MARIS MEDAN - Dian Zuiatna (Nursing Arts, 2020)
ABSTRACTBackground:One of the basic concepts of delivery care with sectio caesaria is early mobilization. Delay inearly mobilization after sectio caesaria can slow healing so it is at risk of experiencing complications due tosurgery. Based on the initial survey at Stella Maris Hospital, it was found that 80% of mothers felt veryafraid to carry out early mobilization. This study: aims to determine the relationship of patient motivationwith the implementation of early mobilization post sectio caesaria in RSIA Stella Maris Medan in 2019. Thistype of research is cross sectional. The sample of this study was mothers after sectio caesaria taken byaccidental sampling technique of 35 people. Data were analyzed by conducting Chi-square analysis. Theresults: showed that the mother's motivation variable had a significant relationship with the variableimplementation of early mobilization of mothers after sectio caesaria at a significant level of 0.011. Mostmothers are aware that mobilizing as early as possible will accelerate healing (intellectual motivation). Mostmothers also often do early mobilization because it is helped by the family (extrinsic motivation).Conclusion: that there is a relationship of motivation with the implementation of early mobilization postsectio caesaria in RSIA Stella Maris Medan in 2019. It is recommended to the RSIA Stella Maris Medan tofurther improve support for patients in carrying out early mobilization after sectio caesaria; Earlymobilization is carried out in accordance with the procedure so that the wound healing process is normal.Keywords: Motivation, Implementation of Post Sectio Caesaria Early MobilizationABSTRAKSalah satu konsep dasar perawatan persalinan dengan sectio caesaria adalah mobilisasi dini.Keterlambatan melakukan mobilisasi dini pasca sectio caesaria dapat memperlambat penyembuhan sehinggaberesiko mengalami komplikasi akibat operasi. Berdasakan survei awal di RSIA Stella Maris, diketahuibahwa 80% ibu merasa sangat takut untuk melakukan mobilisasi dini. Tujuan: untuk mengetahui hubunganmotivasi pasien dengan pelaksanaan mobilisasi dini pasca sectio caesaria di RSIA Stella Maris MedanTahun 2019. Jenis penelitian adalah cross sectional. Sampel penelitian ini adalah ibu pasca sectio caesariayang diambil dengan teknik accidental sampling sebanyak 35 orang. Data dianalisis dengan melakukan ujianalisis Chi-square. Hasil: penelitian menunjukkan variabel motivasi ibu memiliki hubungan yang signifikandengan variabel pelaksanaan mobilisasi dini ibu pasca sectio caesaria pada taraf signifikan 0,011. Sebagianbesar ibu sadar bahwa melakukan mobilisasi sedini mungkin akan mempercepat penyembuhan (motivasiintrisik). Sebagian besar ibu juga sering melakukan mobilisasi dini karena dibantu oleh keluarga (motivasiekstrinsik). Kesimpulan: bahwa ada hubungan motivasi dengan pelaksanaan mobilisasi dini pasca sectiocaesaria di RSIA Stella Maris Medan tahun 2019. Disarankan kepada pihak RSIA Stella Maris Medan agarlebih meningkatkan dukungan kepada pasien dalam melaksanakan mobilisasi dini pasca sectio caesaria;mobilisasi dini dilaksanakan sesuai dengan prosedur agar proses penyembuhan luka normal.Kata Kunci : Motivasi, Pelaksanaan Mobilisasi Dini Pasca Sectio Caesaria